Dulcet Co.: Terminal year-end report - Jamlang, Ashley Nicole P. (Animo Repository, 2022)
Dulcet Co. is focused on selling and manufacturing home decor accessories. Dulcet Co. aims to provide a sense of serenity for society by providing fragrance oils with calming properties and diffusers to disperse the aroma in any space. There are two types of products offered which are the ultrasonic diffuser and the fragrance oil. The founders understood the pandemic caused a big effect on people whether it was a decline from traveling or a decline in one’s mental health. Along with this, the diffuser and fragrance oil industry tends to be difficult to enter due to it being expensive making it more of a luxury to have. Which led to the creation of Dulcet Co. which supported these people and had budget-friendly prices for people who haven’t entered the diffuser and fragrance market to give them a chance to experience entering these kinds of products and industry.